2011
DOI: 10.1105/tpc.110.081067
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana High-Affinity Phosphate Transporters Exhibit Multiple Levels of Posttranslational Regulation  

Abstract: In Arabidopsis thaliana, the PHOSPHATE TRANSPORTER1 (PHT1) family encodes the high-affinity phosphate transporters. They are transcriptionally induced by phosphate starvation and require PHOSPHATE TRANSPORTER TRAFFIC FACILITATOR (PHF1) to exit the endoplasmic reticulum (ER), indicating intracellular traffic as an additional level of regulation of PHT1 activity. Our study revealed that PHF1 acts on PHT1, upstream of vesicle coat protein COPII formation, and that additional regulatory events occur during PHT1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
262
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(274 citation statements)
references
References 53 publications
11
262
0
1
Order By: Relevance
“…5, A and B). The ER location of PHF1 has been confirmed in Arabidopsis (Gonzalez et al, 2005;Bayle et al, 2011). Our data showed that OsPHF1 is also located in ER (Fig.…”
Section: Osphf1 Regulates the Plasma Membrane Localization Of Low-andsupporting
confidence: 63%
See 2 more Smart Citations
“…5, A and B). The ER location of PHF1 has been confirmed in Arabidopsis (Gonzalez et al, 2005;Bayle et al, 2011). Our data showed that OsPHF1 is also located in ER (Fig.…”
Section: Osphf1 Regulates the Plasma Membrane Localization Of Low-andsupporting
confidence: 63%
“…Recently, PHF1 as a PHT1-specific facilitator required for PHT1 transiting through the ER to plasma membrane has been demonstrated. In the posttranslational regulation of PHT1, phosphorylation of PHT1 modulates ER exit and targeting to the plasma membrane that is conserved in PHT1 (Bayle et al, 2011). Additional evidence to the function of PHF1 in regulation of Pi uptake has been reported from its function involved in the excessive leaf Pi accumulation in nitrogen limitation adaptation (nla) mutant at low-NO 3 2 supply (Kant et al, 2011).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, the resolutions in these experiments were far from that obtained here, where it was possible to clearly visualize the labelling of the meristem area, distinct from the uptake at the level of root hairs above the area of differentiation. This clearly illustrates the importance of the role of the PHT1 family of phosphate transporters, which have recently been shown to be strongly expressed in the root cap of Arabidopsis [18].…”
Section: Results and Discussion (A) Real-time Macroscopic Imagingmentioning
confidence: 97%
“…Known targets of the endocytic trafficking route in plants include the auxin carriers PIN1, PIN2, and AUX1, the iron transporter IRT1, the boric acid/borate exporter BOR1, the flagellin receptor FLS2, the brassinosteroid receptor BRI1, and the high-affinity phosphate transporter PHT1 (Barberon et al, 2011;Bayle et al, 2011;Geldner et al, 2001;Kasai et al, 2011;Kleine-Vehn et al, 2006;Kleine-Vehn et al, 2008;Spallek et al, 2013;Spitzer, et al, 2009). (Slagsvold et al, 2006).…”
Section: Discussionmentioning
confidence: 99%